Combining transcriptomes and ultraconserved elements to illuminate the phylogeny of Apidae - Bossert, Silas; Murray, Elizabeth A.; Almeida, Eduardo A.B.; Brady, Seán G.; Blaimer, Bonnie B.; Danforth, Bryan N. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •Sequences of ultraconserved elements and transcriptomes often overlap and can be combined.•A large phylogeny of Apidae resolves controversial nodes.•Cleptoparasitism among orchid bees evolved once and follows Emery’s rule.•The tribe Centridini is the sister group to the corbiculates.•A revised classification of Apidae ensures a rank-based taxonomy of monophyletic groups. Two increasingly popular approaches to reconstruct the Tree of Life involve whole transcriptome sequencing and the target capture of ultraconserved elements (UCEs). Both methods can be used to generate large, multigene datasets for analysis of phylogenetic relationships in non-model organisms. While targeted exon sequencing across divergent lineages is now a standard method, it is still not clear if UCE data can be readily combined with published transcriptomes. In this study, we evaluate the combination of UCEs and transcriptomes in a single analysis using genome-, transcriptome-, and UCE data for 79 bees in the largest and most biologically diverse bee family, Apidae. Using existing tools, we first developed a workflow to assemble phylogenomic data from different sources and produced two large nucleotide matrices of combined data. We then reconstructed the phylogeny of the Apidae using concatenation- and coalescent-based methods, and critically evaluated the resulting phylogenies in the context of previously published genetic, genomic, and morphological data sets. Our estimated phylogenetic trees are robustly supported and largely congruent with previous molecular hypotheses, from deep nodes to shallow species-level phylogenies. Moreover, the combined approach allows us to resolve controversial nodes of the apid Tree of Life, by clarifying the relationships among the genera of orchid bees (Euglossini) and the monophyly of the Centridini. Additionally, we present novel phylogenetic evidence supporting the monophyly of the diverse clade of cleptoparasitic Apidae and the placement of two enigmatic, oil-collecting genera (Ctenoplectra and Tetrapedia). Lastly, we propose a revised classification of the family Apidae that reflects our improved understanding of apid higher-level relationships.